Incorporating conducting polypyrrole into a polyimide COF for carbon-free ultra-high energy supercapacitor - Haldar, Sattwick; Rase, Deepak; Shekhar, Pragalbh; Jain, Chitvan; Vinod, Chathakudath Prabhakaran; Zhang, En; Shupletsov, Leonid; Kaskel, Stefan; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2022)
Redox-active covalent organic frameworks (COFs) store charges but possess inadequate electronic conductivity. Their capacitive action works by storing H+ ions in an acidic electrolyte and is typically confined to a small voltage window (0-1 V). Increasing this window means higher energy and power density, but this risks COF stability. Advantageously, COF's large pores allow the storage of polarizable bulky ions under a wider voltage thus reaching higher energy density. Here, a COF-electrode-electrolyte system operating at a high voltage regime without any conducting carbon or redox active oxides is presented. Conducting polypyrrole (Ppy) chains are synthesized within a polyimide COF to gain electronic conductivity (approximate to 10 000-fold). A carbon-free quasi-solid-state capacitor assembled using this composite showcases high pseudo-capacitance (358 mF cm(-2)@1 mA cm(-2)) in an aqueous gel electrolyte. The synergy among the redox-active polyimide COF, polypyrrole and organic electrolytes allows a wide-voltage window (0-2.5 V) leading to high energy (145 mu Wh cm(-2)) and power densities (4509 mu W cm(-2)). Amalgamating the polyimide-COF and the polypyrrole as one material minimizes the charge and mass transport resistances. Computation and experiments reveal that even a partial translation of the modules/monomers intrinsic electronics to the COF imparts excellent electrochemical activity. The findings unveil COF-confined polymers as carbon-free energy storage materials.
Keywords: carbon free capacitors; cation-anion co-storage; conductivity; high energy capacitors; polypyrrole doped COFs

Exploring defect-engineered metal-organic frameworks with 1,2,4-triazolyl isophthalate and benzoate linkers - Chetry, Sibo; Lukman, Muhammad Fernadi; Bon, Volodymyr; Warias, Rico; Fuhrmann, Daniel; Moellmer, Jens; Belder, Detlev; Gopinath, Chinnakonda S.; Kaskel, Stefan; Poeppl, Andreas; Krautscheid, Harald (INORGANIC CHEMISTRY, 2024)
Keywords: Separation; spectroscopy; TRIAZOLYL